Applied and theoretical perspectives of performance analysis in sport: Scientific issues and challenges - McGarry, T. (International Journal of Performance Analysis in Sport, 2009)
The scientific analysis of sport performance aims at advancing understanding of game behaviour with a view to improving future outcomes. In this article we outline some scientific issues for performance analysis and point towards some possible directions for increased attention in future research. Thus, six inter-linking issues for game analysis are presented for consideration and summarized as follows: First, increased attention should be paid to further developing an understanding of the associations between sports behaviours and sports outcomes; Second, the sports actions observed may not be of equal merit and, instead, some behaviours may be more significant than other behaviours; Third, the interactions between opposing players and/or teams is key for interpreting game behaviour; Fourth, the context in which the sports behaviours are produced offer important information for game analysis; Fifth, the behaviours of players both with and without possession of the sports article must be considered for a complete assessment of game performance, and; Sixth, the player-player dyads constitute a basic unit of analysis for investigating the space-time dynamics of game behaviour. The invitation made here is for a systematic undertaking of each of these inter-linking challenges in future research investigations of sport performance.